Differential effects of defibrillation on systemic and cardiac sympathetic activity. Issue 6 (1st June 1998) - Bode, F; Wiegand, U; Raasch, W; Richardt, G; Potratz, J
Abstract : Objective: To assess the effect of defibrillation shocks on cardiac and circulating catecholamines. Design: Prospective examination of myocardial catecholamine balance during dc shock by simultaneous determination of arterial and coronary sinus plasma concentrations. Internal countershocks (10–34 J) were applied in 30 patients after initiation of ventricular fibrillation for a routine implantable cardioverter defibrillator test. Another 10 patients were externally cardioverted (50–360 J) for atrial fibrillation. Main outcome measures: Transcardiac noradrenaline, adrenaline, and lactate gradients immediately after the shock. Results: After internal shock, arterial noradrenaline increased from a mean (SD) of 263 (128) pg/ml at baseline to 370 (148) pg/ml (p = 0.001), while coronary sinus noradrenaline fell from 448 (292) to 363 (216) pg/ml (p = 0.01), reflecting a shift from cardiac net release to net uptake. After external shock delivery, there was a similar increase in arterial noradrenaline, from 260 (112) to 459 (200) pg/ml (p = 0.03), while coronary sinus noradrenaline remained unchanged. Systemic adrenaline increased 11-fold after external shock (p = 0.01), outlasting the threefold rise following internal shock (p = 0.001). In both groups, a negative transmyocardial adrenaline gradient at baseline decreased further, indicating enhanced myocardial uptake. Cardiac lactate production occurred after ventricular fibrillation and internal shock, but not after external cardioversion, so the neurohumoral changes resulted from the defibrillation process and not from alterations in oxidative metabolism. Conclusions: A dc shock induces marked systemic sympathoadrenal and sympathoneuronal activation, but attenuates cardiac sympathetic activity. This might promote the transient myocardial depression observed after electrical discharge to the heart.